PROFIL GAYA BELAJAR PESERTA DIDIK DAN IMPLIKASINYA BAGI PROGRAM BIMBINGAN BELAJAR - Nurfauziyyah, Hanifah; Khairun, Deasy Yunika (JIEGC Journal of Islamic Education Guidance and Counselling, 2022)
This research is motivated by the problem of learning styles of 8th grade students of SMP Terpadu Al-Qudwah for the 2019/2020 academic year. The purpose of this study was to find out how the profile of learning styles used by full day school students in 8th grade of SMP Terpadu Al-Qudwah. The type of research used in this research is descriptive with a population of 95 students in class VII SMP Terpadu Al-Qudwah which was then narrowed down again using the slovin formula so as to obtain a total sample of 77 students. The data collection method used a learning style questionnaire made by Andriyana Sugiyanto, S.Pd with a reliability level of 0.918. The results showed that the 8th grade students of SMP Terpadu Al-Qudwah who had a visual learning style were 31,2%, while students with an auditory learning style were 62,3% and 6,5% students had a kinesthetic learning style.